Organised crime, corruption and the movement of people across borders in the new enlarged EU: A case study of Estonia, Finland and the UK - Spencer, Jon (Publication series, 2011)
The project reported here is a three-country project, Estonia, Finland and the UK. It is funded by the European Commission AGIS Programme, The Directorate General Justice, Freedom and Security. It investigates the issues of corruption by organised crime in relation to border controls and immigration using as a case study the Finnish-Russian and the Estonian-Russian border. It also considers the methods of facilitation of people across borders, the role of crime groups and networks as well as organised crime and the relationship between illegal facilitation and exploitation in the labour market. The aim of the research was to investigate whether at border points there was evidence of corruption of officials in order to facilitate people across the border illegally. The issue of organised crime was identified as an important factor in understanding how people might be moved across borders illegally. If there was evidence of organised crime it would suggest that transnational networks between organised crime groups might exist and that there are strategic forms of communication between the organised crime groups in order to facilitate the maximisation of profit through the movement of people. If such an influence of organised crime in ‘immigration crime’ were to be discovered then it would indicate that EU borders are porous and therefore readily exploited by organised crime groups. In Finland, particular attention was given to the issues concerning the ‘Development Plan of Border Guards’ and the planned cooperation in relation to Organised Crime and Combating Corruption. The contention was that the EU border with Russia is ‘weak’ and vulnerable to corruption at different levels: systemic, institutional and individual. Our argument was that corruption is used to maintain the flow of people across the border illegitimately by utilising existing legitimate channels. It was the Finnish view that organised crime groups used the Finnish – Russian and the Russian – Estonian borders to bring in illegal immigrants into the EU. Consequently the project was designed to take account of organised immigration crime and so was required to address the issue of human trafficking along with people smuggling and facilitation of people across borders. This raised a number of definitional issues and highlighted the varying perspectives between academic approaches to the problem and those of senior policy makers and operational staff.